Monetary Policy, Financial Stability, and the Zero Lower Bound - Fischer, Stanley (American Economic Review, 2016)
Much has happened in the world of central banking in the past decade. In this paper, I focus on three issues associated with the zero lower bound (ZLB) on short-term nominal interest rates and the nexus between monetary policy and financial stability: 1) whether we are moving toward a permanently lower long-run equilibrium real interest rate; 2) what steps can be taken to mitigate the constraints imposed by the ZLB; and 3) whether and how financial stability considerations should be incorporated in the conduct of monetary policy. These important topics deserve the attention of both academic and government professionals.